2006
DOI: 10.1037/0278-7393.32.4.734
|View full text |Cite
|
Sign up to set email alerts
|

Cued recall from image and sentence memory: A shift from episodic to identical elements representation.

Abstract: ) to cued recall from episodic (image and sentence) memory was explored in 3 transfer experiments. In agreement with results from arithmetic, speedup following even minimal practice recalling a missing word from an episodically bound word triplet did not transfer positively to other cued recall items involving the same triplet. The shape of the learning curve further supported a shift from episode-based to IE-based recall, extending some models of skill learning to cued recall practice. In contrast with previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
30
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 38 publications
3
30
0
Order By: Relevance
“…The predicted and observed result is no positive transfer of practice effects to tested-inverted items. The IE model also correctly predicts the finding that RT improvement during the transition from reliance on the study representation to reliance on the hypothesized recall (testbased) representation does not follow the nearly ubiquitous power law (Newell & Rosenbloom, 1981) for data averaged over subjects, but rather adheres to a mixture function that also characterizes RT learning in other strategy transition contexts (Rickard, 1997;Rickard & Bajic, 2006).…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…The predicted and observed result is no positive transfer of practice effects to tested-inverted items. The IE model also correctly predicts the finding that RT improvement during the transition from reliance on the study representation to reliance on the hypothesized recall (testbased) representation does not follow the nearly ubiquitous power law (Newell & Rosenbloom, 1981) for data averaged over subjects, but rather adheres to a mixture function that also characterizes RT learning in other strategy transition contexts (Rickard, 1997;Rickard & Bajic, 2006).…”
mentioning
confidence: 77%
“…Specificity of learning and testing on triple associates To explain the specificity of learning in the above RT studies, Rickard et al (1994;Rickard & Bajic 2006) proposed an identical-elements (IE) model of retrieval practice effects for multi-element stimuli. According to that model, successful retrieval through a study representation establishes a new and separate recall representation for the particular stimulusresponse configuration that was tested.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In doing single-digit multiplication, children may initially perform a repeated addition algorithm, but with sufficient practice they will transition to direct retrieval (e.g., Siegler, 1988). Multiple laboratory studies have confirmed the ubiquity of this shift for arithmetic and arithmetic-like tasks (Delaney, Reder, Staszewski, & Ritter, 1998;Jenkins & Hoyer, 2000;Logan, 1988Logan, , 1992Onyper, Hoyer, & Cerella, 2006;Palmeri, 1997;Reder & Ritter, 1992;Rickard, 1997Rickard, , 1999Rickard, , 2004Rogers, Hertzog, & Fisk, 2000;Schunn, Reder, Nhouyvanisvong, Richards, & Stroffolino, 1997;Touron, Hoyer, & Cerella, 2001.Similar shifts from algorithmic (defined broadly) to retrievalbased performance are believed to occur in a wide variety of nonarithmetic domains, including recall from episodic memory (Rickard & Bajic, 2006), the shift from mnemonically mediated to unmediated memory retrieval (Kole & Healy, 2007;Rickard & Bajic, 2003), lexical decision (Logan, 1988), word reading (e.g., Tao & Healy, 2002), and text comprehension (Rawson, 2004). Similar shifts may occur under item repetition conditions for visuospatial tasks such as mental rotation (Kail, 1986).…”
mentioning
confidence: 88%
“…Similar shifts from algorithmic (defined broadly) to retrievalbased performance are believed to occur in a wide variety of nonarithmetic domains, including recall from episodic memory (Rickard & Bajic, 2006), the shift from mnemonically mediated to unmediated memory retrieval (Kole & Healy, 2007;Rickard & Bajic, 2003), lexical decision (Logan, 1988), word reading (e.g., Tao & Healy, 2002), and text comprehension (Rawson, 2004). Similar shifts may occur under item repetition conditions for visuospatial tasks such as mental rotation (Kail, 1986).…”
mentioning
confidence: 99%